STRATEGI PENGEMBANGAN WILAYAH MADURA PASCA PEMBANGUNAN JEMBATAN SURAMADU PERIODE 2010-2014 - Lilik Purwantini; Ahmad Zafrullah Tayibnapis; Bambang Budiarto (Jurnal Ekonomi dan Bisnis, 2015)
This study aimed to analyze the strategy of regional development in Madura after Suramadu Bridge began operating between 2010 to 2014. In this study, the object used is the regional development of Madura. This study used a qualitative approach and data used are secondary data obtained from Badan Pusat Statistik (BPS). Results from this study indicate that the regional development in Madura after Suramadu bridge began operating hasn’t achieve the expectation, both from the government and from the folks itself.